2013
DOI: 10.1111/hae.12168
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HLA alleles and cytokine polymorphisms on inhibitors development in children with severe haemophilia A

Abstract: Human Leucocyte Antigen (HLA) alleles, cytokine polymorphisms and the type of factor VIII (FVIII) gene mutation are among predisposing factors for inhibitors (inh) development in children with severe haemophilia A (HA). The aim was to investigate the correlations among (i) FVIII gene intron-22 inversion, (ii) HLA alleles and haplotypes and (iii) certain cytokine polymorphisms, with the risk for FVIII inhibitors development in 52 Greek severe HA children, exclusively treated with recombinant concentrates. We pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…In a study in the UK, the incidence of DRB1*01 , DQB1*05:01 were found to be increased in the inhibitor positive patients, but were not statistically significant . In a Greek cohort however, DRB1*01 , DRB1*01:01 and DQB1*05:01 were reported as possibly promoting inhibitor development, and DRB1*11 , DRB1*11:01 , DQB1*03 and DQB1*03:01 as possibly protecting from inhibitor development . These alleles were not significantly associated with inhibitor development in the Indian population.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…In a study in the UK, the incidence of DRB1*01 , DQB1*05:01 were found to be increased in the inhibitor positive patients, but were not statistically significant . In a Greek cohort however, DRB1*01 , DRB1*01:01 and DQB1*05:01 were reported as possibly promoting inhibitor development, and DRB1*11 , DRB1*11:01 , DQB1*03 and DQB1*03:01 as possibly protecting from inhibitor development . These alleles were not significantly associated with inhibitor development in the Indian population.…”
mentioning
confidence: 58%
“…FVIII administered to congenital severe HA patients acts as an exogenous antigen and triggers an immune response in patients, that involves the human leukocyte antigen (HLA) type II molecules, along with antigen‐presenting cells, T‐ and B‐ lymphocytes in the production of alloantibodies to FVIII. Considering this fact, and also that certain HLA type II DRB1‐ and DQB1‐ alleles especially were found to be significantly more frequent in certain populations , this study was undertaken. The aim was to analyse the frequency of HLA‐DRB1 and HLA‐DQB1 alleles in Indian severe HA patients with inhibitors, and compare it to those without inhibitors to examine if these HLA type II alleles could play a significant role in the differential immune response to FVIII replacement therapy, and predispose to inhibitor development.…”
mentioning
confidence: 99%
“…For instance, we found variants in the HLA class II genes, HLA DRB1 and HLA DRB5, which have an essential role in presenting FVIII peptides to CD4 1 T-helper cells. [11][12][13][14] The HLA DRB1 locus is particularly interesting as it has been shown to be, together with the HLA DQB1, the most consistent risk factor in inhibitor development. 9,13 We also identified variants that may affect the production or function of the immunoglobulin molecules: 5 immunoglobulin heavy chain variable regions, 3 variants in the immunoglobulin k variable cluster, and SNVs in immunoglobulin constant heavy g chains (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…These are summarized in Table 1. [40][41][42][43][44][45][46][47][48][49][50][51][52] Based on current understanding, it seems unlikely that a single marker of significantly greater importance than multiple others will be identified. In fact, the associations found between polymorphic genes and inhibitory antibodies have not been consistent across study cohorts, and the question, of course, is why?…”
Section: Immune Response Genesmentioning
confidence: 99%